THE EFFECT OF HUMOR ORIENTATION ON TEAM PERFORMANCE WITH MEDIATING ROLE OF WORKPLACE BULLYING - Aslam, Sadia; Munawar, Sheraz; Sumal, Maira; Khan, Zeeshan; Akram, Dr.Muhammad Wasim (The journal of contemporary issues in business and government, 2021)
Workplace bullying is associated with a host of negative outcomes for the worker who is the target of bullying, as well as for the organization where the bullying occurs. Moreover, the rates of bullying are particularly high in media houses; however, we are less familiar with the factors like humor orientation that may reduce workplace bullying in media houses. Thus, this study was conducted to determine the effect of humor orientation on team performance with mediating role of workplace bullying. Ego depletion theory has been followed in this paper where a quantitative deductive approach is used for the collection of the data from 200 respondents of Pakistan media houses based in Islamabad. A cross-sectional study is used for this study. Statistical Package for the Social Sciences (SPSS) is used to examine the hypotheses. The results of this study indicate the significant effect of humor orientation on team performance and non-significant relationship between workplace bullying and team performance. A recommendation for future research is to examine whether this outcome can be recreated in different nations around the world. Another proposal is to test workplace bullying effect on project success.